2022
DOI: 10.1126/sciadv.abn5345
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-sensing glucagon-like peptide-1 receptor neurons in the dorsomedial hypothalamus regulate glucose metabolism

Abstract: Glucagon-like peptide-1 (GLP-1) regulates energy homeostasis via activation of the GLP-1 receptors (GLP-1Rs) in the central nervous system. However, the mechanism by which the central GLP-1 signal controls blood glucose levels, especially in different nutrient states, remains unclear. Here, we defined a population of glucose-sensing GLP-1R neurons in the dorsomedial hypothalamic nucleus (DMH), by which endogenous GLP-1 decreases glucose levels via the cross-talk between the hypothalamus and pancreas. Specifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…Moreover, the stable and fasting-disregard blood glucose levels and hyperinsulinemia suggest that the reorganized glucose homeostasis in QIH is not responsive to body energy states. The brain particularly hypothalamic nuclei such as the ARC, ventromedial hypothalamus (VMH), dorsomedial hypothalamus (DMH), and PVN play a critical role in sensing blood glucose, which can reflect energy levels to regulate whole-body energy metabolism (Alvarsson and Stanley, 2018; Huang et al, 2022; Shimazu and Minokoshi, 2017). We showed that QIH universally silences neuronal activity, at least in the ARC.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the stable and fasting-disregard blood glucose levels and hyperinsulinemia suggest that the reorganized glucose homeostasis in QIH is not responsive to body energy states. The brain particularly hypothalamic nuclei such as the ARC, ventromedial hypothalamus (VMH), dorsomedial hypothalamus (DMH), and PVN play a critical role in sensing blood glucose, which can reflect energy levels to regulate whole-body energy metabolism (Alvarsson and Stanley, 2018; Huang et al, 2022; Shimazu and Minokoshi, 2017). We showed that QIH universally silences neuronal activity, at least in the ARC.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the stable and fasting-disregard blood glucose levels and hyperinsulinemia suggest that the reorganized glucose homeostasis in QIH is not responsive to body energy states. The brain particularly hypothalamic nuclei such as the ARC, ventromedial hypothalamus (VMH), dorsomedial hypothalamus (DMH), and PVN play a critical role in sensing blood glucose, which can reflect energy levels to regulate whole-body energy metabolism 10,29,30 . We showed that QIH universally silences neuronal activity, at least in the ARC.…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, it would be preferable to operate bioelectronic implants using an endogenous power source for self‐sufficient, continuous, and reliable operation. In principle, body fluids contain sufficient excess metabolic energy in the form of fatty acids, [ 56 ] and glucose, [ 57 ] which could be harnessed to power bioelectronic implants as well as wearable electronic devices. Since fatty acid metabolism is functionally linked with glucose production via gluconeogenesis.…”
Section: Discussionmentioning
confidence: 99%